Understanding Countries' Tax Effort - Committeri, Marco (IMF Working Papers; Working Paper ;, 2013)
This paper presents a model to determine the tax effort and tax capacity of 113 countries and the main variables on which they depend. The results and the model allow a clear determination of which countries are near their tax capacity and which are some way from it, and therefore, could increase their tax revenue. This paper also determines central factors on which tax capacity depends: the level of development, trade, education, inflation, income distribution, corruption, and the ease of tax collection.